Peningkatan Kemampuan Mengenal Emosi pada Anak Tunagrahita melalui Kegiatan Konseling Kelompok Berbasis Ekspresi Diri - Vera Sriwahyuningsih; Ananda Maha Putri; Mufadhal Barseli (Jurnal Pengabdian Masyarakat Dharma Andalas, 2026)
This community service activity aimed to improve the ability of children with intellectual disabilities to recognize and express emotions through group counseling based on self-expression at Panti Sosial Bina Grahita Harapan Padang. The activities were conducted using emotion cards, facial expression exercises, drawing activities, and simple role-playing. Evaluation was carried out through pre-test and post-test assessments of participants’ emotional abilities. The results showed an increase in the ability to recognize emotions from 42% to 78% (+36%) and the ability to express emotions from 38% to 74% (+36%). In addition, participants demonstrated improved participation, communication confidence, and social interaction during the activities. These findings indicate that self-expression-based group counseling is effective in supporting the social-emotional development of children with intellectual disabilities.